Anticoagulant Activity of Mangrove (Avicennia alba) Leaves Extract in Vitro - Riza Rusyiana; Ima Arum Lestarini; Candra Dwipayana Hamdin; Handa Muliasari (Marine Science Department Diponegoro University, 2021)
Anti-coagulants are substances used to prevent the formation of thromboembolism, one of the causes of cardiovascular disease. Since cardiovascular is a disease as the leading cause of death in the world, exploration of novel and more effective anticoagulant is very needed. Mangroves contain flavonoid and sulphated polysaccharide compounds that potential as anti-coagulants. This study aimed to determine the anti-coagulant activity of ethanol extract and fractions of mangrove leaves (Avicennia alba) in human blood cells in vitro. A. alba leaves were collected at Teluk Ekas, East Lombok, Indonesia. The leaves were macerated with 96% ethanol (3x24h) and then evaporated. The extract was then fractionated to obtain the n-hexane, chloroform, and residual fractions. Anti-coagulant activity of ethanol extract and the three fractions were tested in vitro to five human blood samples by the method of Lee-White and Eustrek, compared to heparin as a positive control. Phytochemical screening of the ethanol extract indicated that A. alba leaves extract contains alkaloids, tannin, saponin, flavonoids, sulphated polysaccharide, and terpenoid. The results of Lee-White method were the ethanol extract (1 mg.mL-1), and three fractions (0.5 mg.mL-1) have anti-coagulant activity. Statistical analysis showed that the anti-coagulant activity of the ethanol extract was significantly different (P<0.05) compared to the normal group and fractions and were not significantly different (P>0.05) compared to heparin. Ethanol extract and the three fractions of A. alba leaves have anti-coagulant activity in vitro. The anti-coagulant activity of ethanol extract (1 mg.mL-1) was comparable to heparin (25 IU) and was better than the three extract fractions (0.5 mg.mL-1). Further research is needed to test the anticoagulant activities of isolated sulphated polysaccharides and flavonoid that can be developed as anticoagulant agents.